QUALITY EVALUATION OF INDIAN GOOSEBERRY (EMBLICA OFFIDNALIS GAERTN.) BASED TRADITIONAL PICKLE ‘KARINELLIKKA’ - E.R, Aneena; C.L, Sharon; Panjikkaran, Seeja Thomachan (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2015)
Karinellikka, an Indian gooseberry based product similar to pickle can be prepared with natural ingredients and have excellent nutritional as well as storage qualities. Karinellikka had the total carbohydrate content of 12.88 per cent. Karinellikka contain high amount of Vitamin C (165.65mg). Unlike other pickle like products, Karinellikka is low in sodium (2.28 mg/100g) but high in potassium (172.5mg/100g). Karinellikka stored in poly ethane laminated aluminium packing (PLM) retained sensory qualities and prolonged the shelf life of the product up to 5 months. The total microbial count of Karinellikka was considerably less upto 3 months in all the three packaging materials and under two storage conditions. Karinellikka can be prepared with natural ingredients and can be marketed without any artificial ingredients or preservatives. Karinellikka an Indian gooseberry based preserved food can be substituted for commercial pickles and have potential to be marketed as a natural product.